Bentuk Perlindungan Hukum Anak terhadap Konten Berbahaya di Media Sosial - Mindyasningrum, Mieke (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
Children are a trust from the Almighty God which we must protect in order to achieve a period of growth and development for a child to become an adult human being for a sustainable future. Apart from that, children are the hope of a nation as the next generation who are expected to become quality individuals. As the nation's next generation, children must be given full protection so that high-quality morals can be formed from an early age. Seeing developments in the current era, the development of social media is growing very rapidly, this cannot be separated from the reach of children even though it is not common. There is a lot of dangerous content on social media, especially violent and pornographic content. Legal protection for children from dangerous content on social media is still general, there are no specific and specific regulations that refer to providing legal protection for children from dangerous content on social media.Keywords: legal protection, children, dangerous content